Influence of substituted pyridines in the chemical behavior of dimethyl sulfoxide ruthenium complexes - Carvalho, Valdemiro P.; Ferraz, Camila P.; Lima-Neto, Benedito S. [UNESP] (Elsevier, 2014)
[RuCl2(S-DMSO)2(X-py)2] type complexes, with X = H (1), 4-CONH2 (2), or 3-CONH2 (3), exhibited trans,cis,cis conformational isomer (species A), with additional cis,cis,cis isomer type (species B) for 1. Electronic spectra with bands in the wavelength range of 270-450 nm were unchanged for 120 min at 25 °C in CH3CN. Irradiation at 350 nm provided replacement of DMSO ligands by CH3CN solvent molecules. Cyclic voltammetry studies in CH3CN revealed an electrochemical-chemical process with a Ru-(S-DMSO) to Ru-(O-DMSO) linkage isomerization for species B from 1. The complexes were inactive for the ring-opening metathesis polymerization (ROMP) of norbornene (NBE) for 60 min at 25°C. However, polyNBE was produced by aging the complex solutions for 90-200 min at 25°C, raising the temperature to 50°C, irradiating the solutions at 350 nm for 5-10 min or when the complexes were in the presence of NBu4ClO4. © 2014 Elsevier B.V. All rights reserved.
Keywords: Ancillary ligand; Dimethyl sulfoxide; Norbornene; Pyridine; ROMP; Ruthenium